A magnetic hierarchical molecularly imprinted polymer nanocomposite adsorbent embedded with a zinc oxide carbon foam for the extraction of sulfonamides - Ananya Kliangsuwan (Prince of Songkla University, 2023)
Master of Science (Chemistry (International Program)), 2022